Wild yet tasty : a guide to edible plants of eastern Kentucky - Dourson, Dan; Dourson, Judy (South Limestone, 2019)
Eastern Kentucky is home to a number of breathtaking natural attractions. Over half a million visitors each year are drawn to its scenic beauty, abundant hiking trails, and exceptional rock climbing. The region also holds some of the most diverse ecosystems in the world, from forest and mountain terrain to caves and ravines. This dramatic mixture of microclimates creates a natural abundance, including numerous edible plants, not found elsewhere in the region. Many are unfamiliar with these fascinating florae species, but Wild Yet Tasty by Dan Dourson and Judy Dourson provides a wealth of information about these comestible, natural treasures. This compact guide provides a useful introduction to the most commonly found and easily identified species, ranging from well-known edibles like morels, blackberries, and persimmons to ones that are not as commonly eaten, such as toothwort, common greenbrier, and redbud. Included are detailed line drawings and descriptions to help with identification, habitat information, specifics on what parts are eatable, and suggestions for the best time to harvest. A glossary of terms and tips for preparing wild food make this guide an invaluable resource for hikers, climbers, and campers visiting the region.